Muscle-fiber specific genetic manipulation of Drosophila sallimus severely impacts neuromuscular development, morphology, and physiology - Michael, Andrew H.; Hana, Tadros A.; Mousa, Veronika G.; Ormerod, Kiel G. (Frontiers in Physiology, 2024)
The ability of skeletal muscles to contract is derived from the unique genes and proteins expressed within muscles, most notably myofilaments and elastic proteins. Here we investigated the role of the sallimus (sls) gene, which encodes a structural homologue of titin, in regulating development, structure, and function of Drosophila melanogaster. Knockdown of sls using RNA interference (RNAi) in all body-wall muscle fibers resulted in embryonic lethality. A screen for muscle-specific drivers revealed a Gal4 line that expresses in a single larval body wall muscle in each abdominal hemisegment. Disrupting sls expression in single muscle fibers did not impact egg or larval viability nor gross larval morphology but did significantly alter the morphology of individual muscle fibers. Ultrastructural analysis of individual muscles revealed significant changes in organization. Surprisingly, muscle-cell specific disruption of sls also severely impacted neuromuscular junction (NMJ) formation. The extent of motor-neuron (MN) innervation along disrupted muscles was significantly reduced along with the number of glutamatergic boutons, in MN-Is and MN-Ib. Electrophysiological recordings revealed a 40% reduction in excitatory junctional potentials correlating with the extent of motor neuron loss. Analysis of active zone (AZ) composition revealed changes in presynaptic scaffolding protein (brp) abundance, but no changes in postsynaptic glutamate receptors. Ultrastructural changes in muscle and NMJ development at these single muscle fibers were sufficient to lead to observable changes in neuromuscular transduction and ultimately, locomotory behavior. Collectively, the data demonstrate that sls mediates critical aspects of muscle and NMJ development and function, illuminating greater roles for sls/titin.